2008
DOI: 10.4049/jimmunol.180.4.2669
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory ITAM Signaling by FcαRI-FcRγ Chain Controls Multiple Activating Responses and Prevents Renal Inflammation

Abstract: Inhibitory signaling is an emerging function of ITAM-bearing immunoreceptors in the maintenance of homeostasis. Monovalent targeting of the IgA Fc receptor (FcαRI or CD89) by anti-FcαRI Fab triggers potent inhibitory ITAM (ITAMi) signaling through the associated FcRγ chain (FcαRI-FcRγ ITAMi) that prevents IgG phagocytosis and IgE-mediated asthma. It is not known whether FcαRI-FcRγ ITAMi signaling controls receptors that do not function through an ITAM and whether this inhibition requires Src homology protein 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 48 publications
(64 reference statements)
4
94
0
Order By: Relevance
“…Previous work showed that monovalent targeting by anti-FcaRI Fab resulted in monocyte apoptosis (47) and prevented or suppressed inflammation in transgenic animal models of renal inflammation (36) and allergic asthma (19). In line with these observations, our study points to an immunoregulatory role for FcaRI, although monovalent targeting of neutrophils by anti-FcaRI Fab had no effect on their viability, and death induction required natural IgA or divalent F(ab9) 2 or whole anti-FcaRI Ab in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work showed that monovalent targeting by anti-FcaRI Fab resulted in monocyte apoptosis (47) and prevented or suppressed inflammation in transgenic animal models of renal inflammation (36) and allergic asthma (19). In line with these observations, our study points to an immunoregulatory role for FcaRI, although monovalent targeting of neutrophils by anti-FcaRI Fab had no effect on their viability, and death induction required natural IgA or divalent F(ab9) 2 or whole anti-FcaRI Ab in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the ligand valence determines the outcome of FcaRI-mediated cellular responses, whereby monovalent receptor targeting by anti-FcaRI Fab has an inhibitory effect, as opposed to polyvalent targeting that results in cellular activation (19,36,37). Therefore, we compared the effects of monovalent antiFcaRI Fab with polyvalent FcaRI targeting on neutrophil viability…”
Section: Differential Susceptibility Of Primed and Resting Neutrophilmentioning
confidence: 99%
“…Conversely, crosslinking of the FcaRI by pIgA causes inflammation by triggering full phosphorylation of FccR and subsequent recruitment of Syk, a protein tyrosine kinase linked to multiple proinflammatory signaling pathways. 30,38 Thus, IgA-containing ICs that are retrotranscytosed across epithelial cells may initiate non-inflammatory or inflammatory immune responses, depending on the monomeric or polymeric nature of the IgA. Monovalent targeting of FcaRI anti-FcaRI Fab fragments prevented asthma or nephritis development in FcaRI transgenic mice.…”
Section: Iga Receptorsmentioning
confidence: 99%
“…Monovalent targeting of FcaRI anti-FcaRI Fab fragments prevented asthma or nephritis development in FcaRI transgenic mice. 30,38 Enhanced FcaRI surface expression has been observed on eosinophils from allergic patients 39 and on monocytes from patients with gram-negative bacteremia. 40 Increased levels of IgA antibodies against allergens and bacterial antigens have been documented in the sputum of atopic asthmatic individuals.…”
Section: Iga Receptorsmentioning
confidence: 99%
“…[6]. We demonstrated the therapeutic potential of an anti-FcαRI Fab treatment for the inhibition of inflammatory responses using two kidney inflammatory models [11]. Cross-linking of the receptor worsened these diseases, whereas treatment with anti-FcαRI Fab impaired inflammatory cell infiltration and fibrosis development.…”
mentioning
confidence: 99%